Cybercrime Case Item Transaction Fraud in DotA Game 2 (Law Research Review Quarterly, 2021)
The DotA 2 Coommunity is known for the largest gamers community in the entire worlds and there is no secrets that this community hub is going bigger and bigger, why this is always expanding is because the game itself offer a complex gameplay with such a huge diversity for the player to explore and enjoy the experience, and the one that this community love most is the microtransacsion in this game that provide the item in game of DotA 2. The value of this item is more and more provitable because the growth of its community and thats make some criminals spread their hand in this community by doing a cybercrime such a scamming, fraud seller and buyer and a hacker that hack someone DotA 2 account that have a provitable account.